Analysis of Solar Power Plants and Its Application for Power Supply of Screw Pumps in Wastewater PT. POMI - Cahyo, Septiyan Eko (Universitas Panca Marga, 2022)
The Cultivation of Domestic wastewater at PT. POMI uses the addition of a screw pump which is carried out to overcome the problem in the storage tank, where the previous submersible pump type cannot work due to changes in the content of wastewater containing fiber, causing the pump impeller get stuck in the waste fiber pump and the pump cannot work. The screw pump is considered to be very powerful and efficient to drain waste containing water, sand, mud and fiber and this pump uses an alternative energy source so that it is more efficient and does not burden the electricity generated by PLN. Utilization of solar energy as a pump resource can reduce the use of fossil fuels used by PLTU as fuel. Measuring the effectiveness of the screw pump is done by sampling to compare the output of waste water entering the reservoir with the screw pump output to the next process. The weather factor is one of the weaknesses of using solar panels. The energy needed to drive a pump of 8.1 kWh requires 21 solar panels with a capacity of 100 Wp which can produce energy of 400 Wh per panel with with parallel 4 configuration with a capacity of 100 Wp per panel.